2003
DOI: 10.1097/00002800-200305000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Rounds

Abstract: Interdisciplinary rounds are a new care coordination strategy in several healthcare settings. This article describes the process used by clinical nurse specialists in one institution to broaden existing discharge planning rounds to interdisciplinary rounds. In addition, a survey queried advanced practice nurse subscribers to two listserves, the ANPACC and CNS-L, to determine how other institutions conducted interdisciplinary rounds, including structure, membership, and leadership. As a result of the changed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Previous research has suggested that staffing patterns and multidisciplinary rounds may influence patient survival. 18,19 In our analyses, we adjusted for patientdoctor ratio and the patient-dialysis staff ratio at facilities, but not for the quality of care by nonphysician staff. The quality of contacts between patients and staff may also be more relevant than its quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that staffing patterns and multidisciplinary rounds may influence patient survival. 18,19 In our analyses, we adjusted for patientdoctor ratio and the patient-dialysis staff ratio at facilities, but not for the quality of care by nonphysician staff. The quality of contacts between patients and staff may also be more relevant than its quantity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a large number of the facilities that we studied (35 clinics [47%]) did not have sit-down rounds, and the larger units in our cohort (more patients per provider and/or more shifts) were less likely to have regular sit-down rounds. Another study showed that resistance of team members to spending time away from the patient was frequently encountered in a hospital setting (3). Such reluctance may also exist in the hemodialysis unit.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that collaborative or interdisciplinary rounds, in which all members of a patient care team discuss each patient's status and develop short-and long-term patient care goals, improve patient care and decrease medical errors in a variety of settings (1)(2)(3). However, most of the evidence that such rounds actually improve patient outcomes is anecdotal in nature.…”
mentioning
confidence: 99%
“…15 It is for these reasons that some work in this area has focused on the individual level of analysis. 6 Despite the need for effective communication in multidisciplinary health care teams, traditional communication tools such as case conferences, interdisciplinary rounds, 30 and discharge planning meetings 31 are often poorly attended or not attended at all by doctors, leaving nurses to take command, sometimes by default rather than by design. Time limitations are often cited as the reason for non-attendance at such planning meetings, however the underlying cause may be an absence of a safety culture that values open communication and holds the team in high regard.…”
Section: Ward-based Teamsmentioning
confidence: 99%